A straightforward approach to high purity sodium silicide Na4Si4. Issue 45 (11th November 2021) - Song, Yang; Gómez-Recio, Isabel; Kumar, Ram; Coelho Diogo, Cristina; Casale, Sandra; Génois, Isabelle; Portehault, David
Abstract : The high reactivity of silicon nanoparticles provides a low temperature pathway to sodium silicide, an important inorganic precursor to silicon-based materials, including clathrates. Abstract : Sodium silicide Na4 Si4 is a reductive and reactive source of silicon highly relevant to designing non-oxidic silicon materials, including clathrates, various silicon allotropes, and metal silicides. Despite the importance of this compound, its production in high amounts and high purity is still a bottleneck with reported methods. In this work, we demonstrate that readily available silicon nanoparticles react with sodium hydride with a stoichiometry close to the theoretical one and at a temperature of 395 °C for shorter duration than previously reported. This enhanced reactivity of silicon nanoparticles makes the procedure robust and less dependent on experimental parameters, such as gas flow. As a result, we deliver a procedure to achieve Na4 Si4 with purity of ca. 98 mol% at the gram scale. We show that this compound is an efficient precursor to deliver selectively type I and type II sodium silicon clathrates depending on the conditions of thermal decomposition.